Experimental study of laminar separation phenomenon combining with numerical calculations - Hung, Nguyen Manh; Bich Ngoc, Hoang Thi (Vietnam Journal of Mechanics, 2011)
The separation is much more sensitive for laminar flow than for turbulent flow. These remarks have been attested for both subsonic and supersonic flows. However, they are not applicable to transonic flows when there are interactions between boundary layer and shock wave. Along with the Reynolds number, the Mach number is a necessary dimensionless parameter for the condition and the mechanism of separations. The report presents one part of studies on laminar separation with Mach number of incompressible flow. The laminar regimes correspond to flows through wind turbine blades. Our experimental work for laminar separation phenomenon was carried out in a subsonic open circuit wind tunnel by taking photographs. The accuracy of experimental results basically depends on the accuracy of wind tunnel and the quality of smoke on density and constitutive materials. Experimental results permit to determine the position of separation and the form of turbulent region followed from the separation point. Numerical studies were simultaneously realized. Based on obtained experimental and numerical results, the report presents also the comparison between the laminar separation and the turbulent separation.